ELECTROLYTE COMPOSITION AND ORAL LIQUID RESISTANCE USED AS PARAMETERS FOR EVALUATING MORPHO-FUNCTIONAL DISTURBANCES INTENSITY IN DENTOALVEOLAR ANOMALIES - D. A. Domenyuk; A. G. Karsueva; I. M. Bykov; A. S. Kochkonyan (Кубанский научный медицинский вестник)
Laboratory-diagnostic methods were used to study specific and non-specific factors of humoral immunity, as well as the electrolyte composition of mixed saliva in children and adolescents aged 7-14 with dentoalveolar anomalies. It has been shown that a reliable index reflecting the intensity of morphological and functional disturbances in case of dentoalveolar anomalies in children and adolescents is an increase in the iron/magnesium ratio gradient with an increased level of sIgA in the oral cavity, as well as a decrease in the potassium/calcium ratio gradient with reduced lysozyme activity and a shift of the hydrogen potential towards alkali.